CULTURAL, ECONOMIC AND POLITICAL SIGNIFICANCE OF THE ORGANIZATION OF TURKIC STATES IN THE EURASIAN REGION - Abdulhamidov , Abdullajon (Scientific practical conference, 2026)
The article cited below discusses the multifaceted importance of the Organization of Turkic States in the Eurasian region. Accordingly, it was tried to provide an explanation of the volume of mutual trade and investment between the countries, as well as their distribution to industries and industries, based on the information provided in open sources.